Strategy and Business Model Reformulation for Development of Zakat, Infaq, Alms, and Waqf (ZISWAF) (Case Study Bank XYZ, Pekanbaru) - Rahman, Aulia; Fahmi, Idqan; Saptono, Imam Teguh (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Indonesia has enormous potential for zakat and waqf, but Bank XYZ has not maximized the collection through the sharia business unit (UUS). Therefore, it is necessary to reformulate the strategy and business model of developing ZISWAF Bank XYZ in order to obtain optimal results. This study used a qualitative descriptive method with a case study at Bank XYZ. The research was conducted from February 2021 to October 2021. The response survey was determined based on purposive sampling consisting of internal practitioners, academics, BWI, BAZNAS, and ziswaf institutions affiliated with Islamic banks. The data collection technique was based on observation, in-depth interviews, and questionnaires to respondents. Data analysis used IPA, BMC, SWOT, and QSPM approaches. Based on IPA analysis, this study recommends that three selected elements be developed: value proposition, channel, and critical resource. Technology adjustment and strengthening of bank image as ZISWAF recipients, improving bank channels through optimizing office networks and utilizing social media marketing and customer databases, as well as improving SOPs to improve the business model of Bank XYZ in the future.